Preparation method of rice hull-based hard carbon negative electrode material
By using rice husks to prepare rice husk-based hard carbon negative electrode materials and perform surface functionalization treatment, the problems of high production cost and poor electrochemical performance of hard carbon electrode materials in the prior art are solved, and the battery performance and service life are achieved. promote.
Patent Information
- Application Number
- CN202411504411.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-26
- Publication Date
- 2025-02-07
AI Technical Summary
The existing hard carbon negative electrode materials have high production costs and poor electrochemical performance, making it difficult to meet the needs of improving battery performance and service life.
The rice husk is used as raw material, and the rice husk-based hard carbon negative electrode material is prepared by deionized water cleaning, drying, grinding and high-temperature calcining. The thiol group is introduced through radio frequency plasma treatment, and Michael addition reaction is carried out to modify the material. surface.
It improves electrochemical performance, enhances charge and discharge efficiency and cycle stability, improves the wetting properties of the electrolyte, thereby improving the overall performance and service life of the battery.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hard carbon negative electrode materials, in particular to a method for preparing a rice husk-based hard carbon negative electrode material. Background Art
[0002] China is the world's largest rice producer, with an annual rice output of more than 200 million tons. As agricultural waste of rice, rice husks also produce more than 100 million tons each year, but there are currently problems of waste and pollution in the treatment of rice husks.
[0003] In recent years, the preparation of carbon materials using a large amount of renewable biomass as raw materials has become a research hotspot. So far, eggshells, tea leaves, onion skins, mushrooms, wool, etc. have been used to prepare carbon materials and successfully applied to electrode materials. In recent years, the preparation of electrode materials using rice husks as raw materials has attracted widespread attention.
[0004] Chinese patent CN108767249B: Provides a method for preparing a hard carbon electrode material, comprising the following steps: heating cotton fibers at 300-400°C under a protective atmosphere, and then grinding them into powder; dissolving polyvinylidene fluoride in N-methylpyrrolidone to obtain a polymer solution; adding the powder to the polymer solution, stirring to obtain a viscous slurry; drying the viscous slurry, heating it to 800-1200°C under a protective atmosphere, and sintering to obtain a hard carbon electrode material; wherein the mass ratio of polyvinylidene fluoride to cotton fibers is 1:5-10. The present invention heats cotton fibers at 300-400°C, then directly mixes them with a polymer solution containing polyvinylidene fluoride, and then sintering them at high temperature to obtain a hard carbon electrode material.
[0005] Chinese patent CN110877908B: discloses a method for preparing a hard carbon electrode material by pyrolysis of corn starch, comprising the following steps: step 1, drying, drying the corn starch to remove moisture; step 2, carbonizing, carbonizing the corn starch obtained in step 1 at high temperature under the protection of an inert gas, and cooling to room temperature to obtain a carbonized material; step 3, punching, mixing the carbonized material obtained in step 2 with KOH evenly, placing it at 700 to 800 degrees Celsius, treating it under the protection of an inert gas, and cooling it to room temperature to obtain a hard carbon electrode material by pyrolysis of corn starch.
[0006] Chinese patent CN113044827B: discloses a method for preparing a nano-carbon composite biomass hard carbon electrode material, which uses biomass as raw material, initially crushes it, washes and dries it; heats it with an alkaline solution, washes and dries it, then crushes it a second time, heats it with an acid solution again to remove excess inorganic salt impurities, washes and dries it; adds a uniformly dispersed acid solution of graphene oxide and carbon nanotubes, stirs and mixes them evenly, treats them with a microwave hydrothermal method, and crushes them a third time after drying to obtain a composite biomass hard carbon precursor; performs low-temperature pre-carbonization and high-temperature treatment on the composite biomass hard carbon precursor under the protection of an inert atmosphere to obtain a composite biomass hard carbon material.
[0007] The hard carbon negative electrode materials prepared by the above patents and prior art have defects such as high production cost and poor electrochemical performance. Summary of the invention
[0008] The purpose of the present invention is to overcome at least one of the problems in the above-mentioned background technology, and to provide a method for preparing a rice husk-based hard carbon negative electrode material, thereby improving the overall performance and service life of the battery.
[0009] The specific plan is as follows:
[0010] A method for preparing a rice husk-based hard carbon negative electrode material, the operating steps of which are:
[0011] S1: Wash the rice husk with deionized water for 3-5 times, dry it at 100-110°C for 8-12h, grind it into powder, and sieve it;
[0012] S2: Weigh 10-20 parts of rice husk powder, 5-10 parts of ferric chloride, 5-10 parts of potassium chloride, and 100-200 parts of deionized water by weight, add them into a reaction kettle, heat to 140-160°C, react for 7-10 hours, filter, and dry at 100-110°C for 8-12 hours;
[0013] S3: placing the dried mixture into a tubular carbonization furnace and calcining it at high temperature under the protection of nitrogen to obtain a hard carbon precursor;
[0014] S4: The hard carbon precursor is repeatedly washed with a hydrochloric acid solution having a mass concentration of 5-10%, then rinsed with deionized water until neutral, and then dried to obtain a rice husk-based porous graphitized activated carbon;
[0015] S5: weigh 60-80 parts by weight of rice husk-based porous graphitized activated carbon, 5-15 parts by weight of carbon black, 1-5 parts by weight of polytetrafluoroethylene, and 80-100 parts by weight of ethanol, mix and stir evenly to obtain a mixed solution;
[0016] S6: Use an electric coating machine to evenly coat the mixed solution on the nickel foam, heat it to 50-70°C and dry it for 8-14 hours;
[0017] S7: After drying, the material is pressed by a tablet press and then subjected to post-treatment and modification to obtain a rice husk-based hard carbon negative electrode material.
[0018] Furthermore, the rice husk powder has a sieved particle size of 300-400 μm.
[0019] Furthermore, the temperature of the tubular carbonization furnace is controlled at 700-900°C for 90-150 minutes.
[0020] Furthermore, the pressure of the tablet press is controlled at 10-15 MPa for 5-10 min.
[0021] Furthermore, the post-processing steps of the rice husk-based hard carbon negative electrode material are:
[0022] H1: The rice husk-based hard carbon negative electrode material is treated by a radio frequency plasma generator to introduce a thiol group (-SH), and the atmosphere is argon gas carrying a small amount of hydrogen sulfide gas; wherein the argon gas flow rate is 10-100mL / min, and the hydrogen sulfide gas flow rate is 0.1-1mL / min; and thiol-modified hard carbon is obtained;
[0023] H2: By mass: Add mercapto-modified hard carbon, vinyl ferrocene, hexafluorobutyl acrylate, and bis(etherfluorene)acrylate into a stirred tank in proportion to carry out Michael addition reaction in anhydrous ethanol with triethylamine as catalyst. After the reaction is completed, filter;
[0024] H3: After filtration, it was washed with deionized water and ethanol and dried under vacuum at 60-80°C.
[0025] Furthermore, the radio frequency power is 60-80W, and the treatment time is 10-30min.
[0026] Furthermore, the mass ratio of the Michael addition reaction is: mercaptolated hard carbon: vinyl ferrocene: hexafluorobutyl acrylate: bisether fluorene acrylate: anhydrous ethanol = 100: 1-5: 0.3-2: 2-6: 1000-1500.
[0027] Furthermore, the reaction temperature of the Michael addition reaction is 50-60° C., and the reaction time is 6-12 h.
[0028] Reaction mechanism
[0029] Michael addition is a type of organic chemical reaction in which thiol (-SH) acts as a nucleophile to attack the β-carbon atom of α, β-unsaturated carbonyl compounds (such as acrylate compounds). In the process of preparing hard carbon negative electrode materials, the thiol introduced by radio frequency plasma treatment can provide hydrogen atoms on the thiol group as good donors, thereby initiating an addition reaction on the double bond in the acrylate compound and converting it into the corresponding thiol product.
[0030] Technical Effects
[0031] The present invention provides a method for preparing a rice husk-based hard carbon negative electrode material. Compared with the prior art, the present invention has the following significant effects:
[0032] 1. The present invention uses rice husk to prepare hard carbon negative electrode materials because it has a unique three-dimensional network structure and contains a large amount of silicon dioxide components, which can serve as a perfect template skeleton in the process of converting to carbon materials; at the same time, using rice husk as raw material can also reduce environmental problems caused by incineration, while reducing production costs, which is in line with the concept of green environmental protection;
[0033] 2. Improve electrochemical performance: Due to the modification of thiol and olefin compounds on the hard carbon surface, the electrochemical activity of the hard carbon negative electrode material and the adsorption capacity of sodium ions are improved, thereby increasing the capacity of the battery;
[0034] 3. Enhanced charge and discharge efficiency: Surface functionalized hard carbon negative electrode materials can reduce the diffusion resistance of sodium ions, making the charge and discharge process more efficient and reducing energy loss;
[0035] 4. Improve cycle stability: Due to the chemical modification of the hard carbon surface, the structural stability is enhanced, so that the battery can still maintain good performance after multiple charge and discharge cycles;
[0036] 5. Improved wettability of electrolyte: The increased carboxylate content on the hard carbon surface allows the electrolyte to penetrate more easily into the electrode material, thereby improving the overall performance and service life of the battery. DETAILED DESCRIPTION
[0037] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation method, structure, characteristics and effects of the present invention are described in detail below in combination with the preferred embodiments.
[0038] Electrochemical energy test: The test was carried out using a CHI660E electrochemical workstation; the specific capacitance was tested at a current density of 1 A / g; after 10,000 cycles at a current density of 1 A / g, the specific capacitance retention rate was tested.
[0039] Example 1
[0040] A method for preparing a rice husk-based hard carbon negative electrode material, the operating steps of which are:
[0041] S1: Wash the rice husk with deionized water three times, dry it at 100 °C for 8 h, grind it into powder, and sieve it;
[0042] S2: Weigh 10g rice husk powder, 5g ferric chloride, 5g potassium chloride, and 100g deionized water, add them into a reactor, heat to 140°C, react for 7h, filter, and dry at 100°C for 8h;
[0043] S3: placing the dried mixture into a tubular carbonization furnace and calcining it at high temperature under the protection of nitrogen to obtain a hard carbon precursor;
[0044] S4: The hard carbon precursor is repeatedly washed with a hydrochloric acid solution having a mass concentration of 5%, then rinsed with deionized water until neutral, and then dried to obtain a rice husk-based porous graphitized activated carbon;
[0045] S5: Weigh 60 g of rice husk-based porous graphitized activated carbon, 5 g of carbon black, 1 g of polytetrafluoroethylene, and 80 g of ethanol, mix and stir evenly to obtain a mixed solution;
[0046] S6: Use an electric coating machine to evenly coat the mixed solution on the nickel foam, heat it to 50°C and dry it for 8 hours;
[0047] S7: After drying, the material is pressed by a tablet press and then subjected to post-treatment and modification to obtain a rice husk-based hard carbon negative electrode material.
[0048] The sieved particle size of the rice husk powder is 300 μm.
[0049] The temperature of the tubular carbonization furnace is controlled at 700° C. for 90 minutes.
[0050] The pressure of the tablet press is controlled at 10 MPa for 5 minutes.
[0051] The post-processing steps of the rice husk-based hard carbon negative electrode material are as follows:
[0052] H1: The rice husk-based hard carbon negative electrode material is treated by a radio frequency plasma generator to introduce a thiol group (-SH), and the atmosphere is argon gas carrying a small amount of hydrogen sulfide gas; the argon gas flow rate is 10mL / min, and the hydrogen sulfide gas flow rate is 0.1mL / min; thiol hard carbon is obtained;
[0053] H2: Add mercapto-modified hard carbon, vinyl ferrocene, hexafluorobutyl acrylate, and bis(etherfluorene)acrylate into a stirred tank in a certain proportion to carry out Michael addition reaction in anhydrous ethanol with triethylamine as catalyst. After the reaction is completed, filter;
[0054] H3: After filtration, it was washed with deionized water and ethanol and dried in vacuum at 60 °C.
[0055] The radio frequency power is 60W and the treatment time is 10 minutes.
[0056] The mass ratio of the Michael addition reaction is: mercaptolated hard carbon: vinyl ferrocene: hexafluorobutyl acrylate: bisether fluorene acrylate: anhydrous ethanol = 100:1:0.3:2:1000.
[0057] The reaction temperature of the Michael addition reaction is 50° C. and the reaction time is 6 h.
[0058] Example 2
[0059] A method for preparing a rice husk-based hard carbon negative electrode material, the operating steps of which are:
[0060] S1: Wash the rice husk with deionized water for 4 times, dry it at 105 °C for 9 h, grind it into powder, and sieve it;
[0061] S2: Weigh 13g rice husk powder, 6g ferric chloride, 6g potassium chloride, and 130g deionized water, add them into a reactor, heat to 145°C, react for 8h, filter, and dry at 105°C for 9h;
[0062] S3: placing the dried mixture into a tubular carbonization furnace and calcining it at high temperature under the protection of nitrogen to obtain a hard carbon precursor;
[0063] S4: The hard carbon precursor is repeatedly washed with a hydrochloric acid solution having a mass concentration of 5%, then rinsed with deionized water until neutral, and then dried to obtain a rice husk-based porous graphitized activated carbon;
[0064] S5: Weigh 65 g of rice husk-based porous graphitized activated carbon, 8 g of carbon black, 2 g of polytetrafluoroethylene, and 85 g of ethanol, mix and stir evenly to obtain a mixed solution;
[0065] S6: Use an electric coating machine to evenly coat the mixed solution on the nickel foam, heat it to 55°C and dry it for 10 hours;
[0066] S7: After drying, the material is pressed by a tablet press and then subjected to post-treatment and modification to obtain a rice husk-based hard carbon negative electrode material.
[0067] The sieved particle size of the rice husk powder is 300 μm.
[0068] The temperature of the tubular carbonization furnace is controlled at 750° C. for 110 minutes.
[0069] The pressure of the tablet press is controlled at 12MPa for 6min.
[0070] The post-processing steps of the rice husk-based hard carbon negative electrode material are as follows:
[0071] H1: The rice husk-based hard carbon negative electrode material is treated by a radio frequency plasma generator to introduce a thiol group (-SH), and the atmosphere is argon gas carrying a small amount of hydrogen sulfide gas; the argon gas flow rate is 50mL / min, and the hydrogen sulfide gas flow rate is 0.5mL / min; thiol hard carbon is obtained;
[0072] H2: Add mercapto-modified hard carbon, vinyl ferrocene, hexafluorobutyl acrylate, and bis(etherfluorene)acrylate into a stirred tank in a certain proportion to carry out Michael addition reaction in anhydrous ethanol with triethylamine as catalyst. After the reaction is completed, filter;
[0073] H3: After filtration, it was washed with deionized water and ethanol and dried in vacuum at 65 °C.
[0074] The radio frequency power is 65W and the processing time is 15 minutes.
[0075] The mass ratio of the Michael addition reaction is: mercaptolated hard carbon: vinyl ferrocene: hexafluorobutyl acrylate: bisether fluorene acrylate: anhydrous ethanol = 100:2:1:3:1100.
[0076] The reaction temperature of the Michael addition reaction is 55° C. and the reaction time is 8 h.
[0077] Example 3
[0078] A method for preparing a rice husk-based hard carbon negative electrode material, the operating steps of which are:
[0079] S1: Wash the rice husk with deionized water for 4 times, dry it at 105 °C for 11 h, grind it into powder, and sieve it;
[0080] S2: Weigh 18g rice husk powder, 8g ferric chloride, 8g potassium chloride, and 180g deionized water, add them into a reactor, heat to 155°C, react for 9h, filter, and dry at 105°C for 11h;
[0081] S3: placing the dried mixture into a tubular carbonization furnace and calcining it at high temperature under the protection of nitrogen to obtain a hard carbon precursor;
[0082] S4: The hard carbon precursor is repeatedly washed with a hydrochloric acid solution having a mass concentration of 10%, then rinsed with deionized water until neutral, and then dried to obtain a rice husk-based porous graphitized activated carbon;
[0083] S5: Weigh 75 g of rice husk-based porous graphitized activated carbon, 13 g of carbon black, 4 g of polytetrafluoroethylene, and 95 g of ethanol, mix and stir evenly to obtain a mixed solution;
[0084] S6: Use an electric coating machine to evenly coat the mixed solution on the nickel foam, heat it to 65°C and dry it for 12 hours;
[0085] S7: After drying, the material is pressed by a tablet press and then subjected to post-treatment and modification to obtain a rice husk-based hard carbon negative electrode material.
[0086] The sieved particle size of the rice husk powder is 400 μm.
[0087] The temperature of the tubular carbonization furnace is controlled at 850° C. for 130 minutes.
[0088] The pressure of the tablet press is controlled at 14 MPa for 8 minutes.
[0089] The post-processing steps of the rice husk-based hard carbon negative electrode material are as follows:
[0090] H1: The rice husk-based hard carbon negative electrode material is treated by a radio frequency plasma generator to introduce a thiol group (-SH), and the atmosphere is argon gas carrying a small amount of hydrogen sulfide gas; the argon gas flow rate is 90 mL / min, and the hydrogen sulfide gas flow rate is 0.9 mL / min; thiol hard carbon is obtained;
[0091] H2: Add mercapto-modified hard carbon, vinyl ferrocene, hexafluorobutyl acrylate, and bis(etherfluorene)acrylate into a stirred tank in a certain proportion to carry out Michael addition reaction in anhydrous ethanol with triethylamine as catalyst. After the reaction is completed, filter;
[0092] H3: After filtration, it was washed with deionized water and ethanol and dried under vacuum at 75 °C.
[0093] The radio frequency power is 75W and the processing time is 25min.
[0094] The mass ratio of the Michael addition reaction is: mercaptolated hard carbon: vinyl ferrocene: hexafluorobutyl acrylate: bisether fluorene acrylate: anhydrous ethanol = 100:4:1.5:5:1400.
[0095] The reaction temperature of the Michael addition reaction is 55° C. and the reaction time is 10 h.
[0096] Example 4
[0097] A method for preparing a rice husk-based hard carbon negative electrode material, the operating steps of which are:
[0098] S1: Wash the rice husk with deionized water for 5 times, dry it at 110 °C for 12 h, grind it into powder, and sieve it;
[0099] S2: Weigh 20g rice husk powder, 10g ferric chloride, 10g potassium chloride, and 200g deionized water, add them into a reactor, heat to 160°C, react for 10h, filter, and dry at 110°C for 12h;
[0100] S3: placing the dried mixture into a tubular carbonization furnace and calcining it at high temperature under the protection of nitrogen to obtain a hard carbon precursor;
[0101] S4: The hard carbon precursor is repeatedly washed with a hydrochloric acid solution having a mass concentration of 10%, then rinsed with deionized water until neutral, and then dried to obtain a rice husk-based porous graphitized activated carbon;
[0102] S5: Weigh 80 g of rice husk-based porous graphitized activated carbon, 15 g of carbon black, 5 g of polytetrafluoroethylene, and 100 g of ethanol, mix and stir evenly to obtain a mixed solution;
[0103] S6: Use an electric coating machine to evenly coat the mixed solution on the nickel foam, heat it to 70°C and dry it for 14 hours;
[0104] S7: After drying, the material is pressed by a tablet press and then subjected to post-treatment and modification to obtain a rice husk-based hard carbon negative electrode material.
[0105] The sieved particle size of the rice husk powder is 400 μm.
[0106] The temperature of the tubular carbonization furnace is controlled at 900° C. for 150 minutes.
[0107] The pressure of the tablet press is controlled at 15 MPa for 10 minutes.
[0108] The post-processing steps of the rice husk-based hard carbon negative electrode material are as follows:
[0109] H1: The rice husk-based hard carbon negative electrode material is treated by a radio frequency plasma generator to introduce a thiol group (-SH), and the atmosphere is argon gas carrying a small amount of hydrogen sulfide gas; the argon gas flow rate is 100mL / min, and the hydrogen sulfide gas flow rate is 1mL / min; thiol hard carbon is obtained;
[0110] H2: Add mercapto-modified hard carbon, vinyl ferrocene, hexafluorobutyl acrylate, and bis(etherfluorene)acrylate into a stirred tank in a certain proportion to carry out Michael addition reaction in anhydrous ethanol with triethylamine as catalyst. After the reaction is completed, filter;
[0111] H3: After filtration, it was washed with deionized water and ethanol and dried in vacuum at 80 °C.
[0112] The radio frequency power is 80W and the treatment time is 30min.
[0113] The mass ratio of the Michael addition reaction is: mercaptolated hard carbon: vinyl ferrocene: hexafluorobutyl acrylate: bisether fluorene acrylate: anhydrous ethanol = 100:5:2:6:1500.
[0114] The reaction temperature of the Michael addition reaction is 60° C. and the reaction time is 12 h.
[0115] Comparative Example 1
[0116] In this example, the rice husk-based hard carbon negative electrode material is not post-treated, and the rest is the same as in Example 1.
[0117] Comparative Example 2
[0118] In this example, no vinylferrocene is added during the post-treatment of the rice husk-based hard carbon negative electrode material, and the rest is the same as in Example 1.
[0119] Comparative Example 3
[0120] In this example, hexafluorobutyl acrylate was not added during the post-treatment of the rice husk-based hard carbon negative electrode material, and the rest was the same as in Example 1.
[0121] Example test results:
[0122] Specific capacitance / F / g Specific capacitance retention rate is / % Example 1 379.5 85.3 Example 2 385.6 86.4 Example 3 391.8 87.6 Example 4 397.4 88.7 Comparative Example 1 268.8 66.6 Comparative Example 2 295.7 74.0 Comparative Example 3 317.2 78.3
[0123] Through the data analysis of the above embodiments and comparative examples, the rice husk-based hard carbon negative electrode material prepared by the present invention has a higher specific capacitance, and after 10,000 cycles at a current density of 1 A / g, the specific capacitance retention rate is high.
[0124] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a rice husk-based hard carbon negative electrode material, the operating steps of which are: S1: Wash the rice husk with deionized water for 3-5 times, dry it at 100-110°C for 8-12h, grind it into powder, and sieve it; S2: Weigh 10-20 parts of rice husk powder, 5-10 parts of ferric chloride, 5-10 parts of potassium chloride, and 100-200 parts of deionized water by weight, add them into a reaction kettle, heat to 140-160°C, react for 7-10 hours, filter, and dry at 100-110°C for 8-12 hours; S3: placing the dried mixture into a tubular carbonization furnace and calcining it at high temperature under the protection of nitrogen to obtain a hard carbon precursor; S4: The hard carbon precursor is repeatedly washed with a hydrochloric acid solution having a mass concentration of 5-10%, then rinsed with deionized water until neutral, and then dried to obtain a rice husk-based porous graphitized activated carbon; S5: weigh 60-80 parts by weight of rice husk-based porous graphitized activated carbon, 5-15 parts by weight of carbon black, 1-5 parts by weight of polytetrafluoroethylene, and 80-100 parts by weight of ethanol, mix and stir evenly to obtain a mixed solution; S6: Use an electric coating machine to evenly coat the mixed solution on the nickel foam, heat it to 50-70°C and dry it for 8-14 hours; S7: After drying, the material is pressed by a tablet press and then subjected to post-treatment and modification to obtain a rice husk-based hard carbon negative electrode material.
2. The method for preparing a rice husk-based hard carbon negative electrode material according to claim 1, characterized in that: The sieved particle size of the rice husk powder is 300-400 μm.
3. The method for preparing a rice husk-based hard carbon negative electrode material according to claim 1, characterized in that: The temperature of the tubular carbonization furnace is controlled at 700-900°C for 90-150 minutes.
4. The method for preparing a rice husk-based hard carbon negative electrode material according to claim 1, characterized in that: The pressure of the tablet press is controlled at 10-15 MPa for 5-10 minutes.
5. The method for preparing a rice husk-based hard carbon negative electrode material according to claim 1, characterized in that: The post-processing steps of the rice husk-based hard carbon negative electrode material are as follows: H1: The rice husk-based hard carbon negative electrode material is treated by a radio frequency plasma generator to introduce a thiol group (-SH), and the atmosphere is argon gas carrying a small amount of hydrogen sulfide gas; wherein the argon gas flow rate is 10-100mL / min, and the hydrogen sulfide gas flow rate is 0.1-1mL / min; and thiol-modified hard carbon is obtained; H2: By mass: Add mercapto-modified hard carbon, vinyl ferrocene, hexafluorobutyl acrylate, and bis(etherfluorene)acrylate into a stirred tank in proportion to carry out Michael addition reaction in anhydrous ethanol with triethylamine as catalyst. After the reaction is completed, filter; H3: After filtration, it was washed with deionized water and ethanol and dried under vacuum at 60-80°C.
6. The method for preparing a rice husk-based hard carbon negative electrode material according to claim 5, characterized in that: The radio frequency power is 60-80W, and the treatment time is 10-30min.
7. The method for preparing a rice husk-based hard carbon negative electrode material according to claim 5, characterized in that: The mass ratio of the Michael addition reaction is: mercaptolated hard carbon: vinyl ferrocene: hexafluorobutyl acrylate: bisether fluorene acrylate: anhydrous ethanol = 100: 1-5: 0.3-2: 2-6: 1000-1500.
8. The method for preparing a rice husk-based hard carbon negative electrode material according to claim 5, characterized in that: The reaction temperature of the Michael addition reaction is 50-60° C., and the reaction time is 6-12 hours.
Citation Information
Patent Citations
A method for preparing hard carbon electrode material
CN108767249B
A method for preparing corn starch pyrolysis hard carbon electrode material
CN110877908B
Nano-carbon composite biomass hard carbon electrode materials, their preparation methods and applications
CN113044827B